Effect of ultrafine powders on the structural formation processes and mechanical properties of Al-7%Si alloy; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Zykova A. P. Anna Petrovna (Materials structure and properties under modification, 2016)
Title screen